Complement-targeted therapeutics in periodontitis - Hajishengallis, George (2013)
Periodontitis is a prevalent oral chronic inflammatory disease which, in severe forms, may exert a major impact on systemic health. Clinical and histological observations, as well as experimental animal studies, suggest involvement of the complement system in periodontitis. However, the precise roles of the various complement components and pathways in periodontitis have only recently started to be elucidated. In this paper, we review recent progress in the field and discuss the potential of complement-targeted therapeutics in the treatment of periodontitis.